Preventing the mental health consequences of war in refugee populations - Barbui Corrado; Purgato Marianna; Acarturk Ceren; Churchill Rachel; Cuijpers Pim; Koesters Markus; Sijbrandij Marit; Välimäki Maritta; Wancata Johannes; White Ross G (CAMBRIDGE UNIV PRESS, 2022)
The refugee experience is associated with several potentially traumatic events that increase the risk of developing mental health consequences, including worsening of subjective wellbeing and quality of life, and risk of developing mental disorders. Here we present actions that countries hosting forcibly displaced refugees may implement to decrease exposure to potentially traumatic stressors, enhance subjective wellbeing and prevent the onset of mental disorders. A first set of actions refers to the development of reception conditions aiming to decrease exposure to post-migration stressors, and a second set of actions refers to the implementation of evidence-based psychological interventions aimed at reducing stress, preventing the development of mental disorders and enhancing subjective wellbeing.